2015
DOI: 10.1002/jmv.24200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of severe hand, foot, and mouth disease in Shenzhen, China, 2009-2013

Abstract: Hand, foot, and mouth disease (HFMD) is caused by human enteroviruses, especially by enterovirus 71 (EV71) and coxsackievirus A16 (CA16). Patients infected with different enteroviruses show varied clinical symptoms. The aim of this study was to determine whether the etiological spectrum of mild and severe HFMD changed, and the association between pathogens and clinical features. From 2009 to 2013, a total of 2,299 stool or rectal specimens were collected with corresponding patient data. A dynamic view of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 42 publications
5
54
1
Order By: Relevance
“…EV‐A71 has usually been identified as the most prevalent pathogen causing serious HFMD, and CV‐A16 is thought to be associated with mild HFMD and self‐limiting symptoms. However, CV‐A16 and other EV types such as CV‐A6, CV‐A10, CV‐A4, and E‐9 have been associated with severe HFMD independently of EV‐A71 . Our study samples were collected from patients with serious HFMD.…”
Section: Discussionmentioning
confidence: 99%
“…EV‐A71 has usually been identified as the most prevalent pathogen causing serious HFMD, and CV‐A16 is thought to be associated with mild HFMD and self‐limiting symptoms. However, CV‐A16 and other EV types such as CV‐A6, CV‐A10, CV‐A4, and E‐9 have been associated with severe HFMD independently of EV‐A71 . Our study samples were collected from patients with serious HFMD.…”
Section: Discussionmentioning
confidence: 99%
“…Our CV-A6 findings are consistent with other reports from the region. 49, 78, 79, 80, 81 CV-A6 progressively became the most common virus detected among mild HFMD cases, apparently replacing other non-EV-A71 viruses, including CV-A16 in China, Thailand, Malaysia and Singapore. 11, 49, 82, 83, 84, 85, 86, 87 CV-A6 seems now to be associated with many outbreaks worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Especially after 2008, HFMD has become a pressing issue for public health in China. EV associated HFMD accompanying aseptic meningitis have been reported, such as EV-A71, CV-A16, CV-A6, CV-A10, CV-A4, and E-9, and some of them have become the main causative agents of aseptic meningitis for epidemics of HFMD (Huang et al 1999, 2015). Our previous study has shown that EV-A71, CV-A16, and E-9 were the most common serotypes detected for HFMD and other serotypes such as CV-A1, CV-A8, CV-A9, CV-A10, CV-B2, CV-B4, E-1, and E-3 have been identified from 2009 to 2011 (Ma et al 2015).…”
Section: Discussionmentioning
confidence: 99%